Ion conductor materials and batteries
By controlling the amount of modified groups in the resin binder to ensure that its material mass ratio is less than 0.0002, the problem of reduced ion conductivity when the halide solid electrolyte material is combined with the resin binder is solved, and the battery charge and discharge efficiency is improved. Lift and thermal stability enhancement.
Patent Information
- Application Number
- CN202080021741.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-26
- Filing Date
- 2020-04-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-04-28
AI Technical Summary
In the prior art, when the halide solid electrolyte material is combined with a resin binder, excessive amount of modified groups in the resin binder leads to a decrease in the ion conductivity of the solid electrolyte material, thereby reducing the charge and discharge efficiency of the battery.
By controlling the material mass ratio of the modified groups contained in the resin binder so that the material mass ratio relative to the solid electrolyte material is 0.0002 or less, the decrease in ion conductivity of the halide solid electrolyte material is suppressed and the adhesive strength is maintained. And improve the charging and discharging efficiency of the battery.
It is possible to improve the charge and discharge efficiency of the battery without reducing the bonding strength of the solid electrolyte material, enhance the thermal stability of the battery and suppress the generation of hydrogen sulfide gas.
Smart Images

Figure CN113597694B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to ionic conductor materials and batteries. Background Art
[0002] Patent Document 1 discloses a battery including a solid electrolyte and a thermoplastic elastomer. In the thermoplastic elastomer, a functional group is introduced to improve the adhesion strength between the solid electrolyte and the positive electrode active material, the adhesion strength between the solid electrolytes, and the adhesion strength between the solid electrolyte and the negative electrode active material.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2017 / 217079 Summary of the invention
[0006] Problems to be solved by the invention
[0007] The present disclosure provides an ion conductor material that improves the charge and discharge efficiency of a battery.
[0008] Methods for solving problems
[0009] An ion conductor material in one embodiment of the present disclosure comprises a solid electrolyte material and a resin binder.
[0010] The solid electrolyte material comprises Li, M and X.
[0011] The above-mentioned M is at least one selected from metal elements and metalloid elements other than Li,
[0012] The above X is at least one selected from F, Cl, Br and I,
[0013] The amount ratio of the modifying group contained in the resin binder to the solid electrolyte material is 0.0002 or less.
[0014] Effects of the Invention
[0015] According to the present disclosure, an ion conductor material that improves the charge and discharge efficiency of a battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic diagram showing the structure of the ion conductor material 1000 involved in the first embodiment.
[0017] Figure 2 This is a cross-sectional view schematically showing the structure of a battery 2000 according to the second embodiment. DETAILED DESCRIPTION
[0018] The ion conductor material according to the first aspect of the present disclosure includes a solid electrolyte material and a resin binder.
[0019] The solid electrolyte material comprises Li, M and X.
[0020] The above-mentioned M is at least one selected from metal elements and metalloid elements other than Li,
[0021] The above X is at least one selected from F, Cl, Br and I,
[0022] The amount ratio of the modifying group contained in the resin binder to the solid electrolyte material is 0.0002 or less.
[0023] When the ion conductor material according to the first embodiment is used in a battery, the charge and discharge efficiency of the battery can be improved.
[0024] In the second aspect of the present disclosure, for example, in the ion conductor material according to the first aspect, the solid electrolyte material may be represented by the following composition formula (1).
[0025] Li α M β X γ Formula (1)
[0026] Wherein, the above α, the above β and the above γ are all values greater than 0,
[0027] According to the ion conductor material of the second embodiment, the ion conductivity of the solid electrolyte material is improved, so the ion conductivity can be improved. Therefore, when the ion conductor material of the second embodiment is used in a battery, the charge and discharge efficiency of the battery can be further improved.
[0028] In a third aspect of the present disclosure, for example, in the ion conductor material according to the first aspect or the second aspect, the M may include yttrium.
[0029] When the ion conductor material according to the third aspect is used in a battery, the charge and discharge efficiency of the battery can be further improved.
[0030] In a fourth aspect of the present disclosure, for example, in the ion conductor material according to any one of the first to third aspects, the resin binder may contain a thermoplastic elastomer.
[0031] According to the ion conductor material according to the fourth aspect, when heat compression is performed during battery production, high filling of the ion conductor material can be achieved.
[0032] In a fifth aspect of the present disclosure, for example, in the ion conductor material according to the fourth aspect, the thermoplastic elastomer may contain a styrene unit.
[0033] Styrene-based thermoplastic elastomers have high electrochemical resistance and high adhesive strength. Therefore, according to the ion conductor material according to the fifth embodiment, the cycle performance of the battery can be improved.
[0034] In a sixth aspect of the present disclosure, for example, in the ion conductor material according to the fifth aspect, the thermoplastic elastomer may be a styrene-ethylene-butylene-styrene copolymer.
[0035] Styrene-ethylene-butylene-styrene copolymer has high electrochemical resistance and high adhesive strength. Therefore, according to the ion conductor material involved in the sixth embodiment, the cycle performance of the battery can be improved.
[0036] In a seventh aspect of the present disclosure, for example, in the ion conductor material according to any one of the first to sixth aspects, the acid value of the resin binder may be 1 mg-CH3ONa / g or less.
[0037] When the ion conductor material according to the seventh aspect is used in a battery, the charge and discharge efficiency of the battery can be further improved.
[0038] An eighth aspect of the present disclosure provides a battery comprising:
[0039] positive electrode;
[0040] a negative electrode; and
[0041] an electrolyte layer disposed between the positive electrode and the negative electrode,
[0042] At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the ion conductor material according to any one of the first to seventh aspects.
[0043] According to the battery according to the eighth aspect, excellent charge and discharge efficiency can be achieved.
[0044] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0045] (Implementation Method 1)
[0046] Figure 1 Schematic diagram showing the structure of the ion conductor material 1000 involved in Embodiment 1. The ion conductor material 1000 in Embodiment 1 includes a solid electrolyte material 101 and a resin binder 102. The solid electrolyte material 101 includes Li, M and X. Among them, M is at least one selected from metal elements and metalloid elements other than Li, and X is at least one selected from F, Cl, Br and I. The amount ratio of the modified group contained in the resin binder 102 to the solid electrolyte material 101 is 0.0002 or less.
[0047] With the above configuration, when the ion conductor material 1000 in Embodiment 1 is used in a battery (for example, an all-solid secondary battery), the charge and discharge efficiency of the battery can be improved.
[0048] In the present disclosure, the so-called "metalloid elements" are B, Si, Ge, As, Sb and Te.
[0049] In addition, in the present disclosure, the so-called "metal element" is:
[0050] (i) all elements included in Groups 1 to 12 of the periodic table except hydrogen; and
[0051] (ii) All elements included in Groups 13 to 16 of the periodic table except B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se.
[0052] That is, in the present disclosure, "metalloid elements" and "metal elements" are a group of elements that can be cations when forming an inorganic compound with a halogen element.
[0053] The ion conductor material 1000 involved in Embodiment 1 is described in detail below. In addition, in the following, the solid electrolyte material 101 is sometimes described as a "halide solid electrolyte material". In addition, the so-called "halide solid electrolyte material" in the present disclosure refers to a solid electrolyte material that contains a halogen element and does not contain sulfur. In addition, in the present disclosure, the so-called solid electrolyte material that does not contain sulfur refers to a solid electrolyte material represented by a composition formula that does not contain a sulfur element. Therefore, extremely trace amounts of sulfur components, such as solid electrolyte materials with sulfur of less than 0.1 mass %, are included in the scope of solid electrolyte materials that do not contain sulfur. The halide solid electrolyte material may further contain oxygen as an anion other than the halogen element.
[0054] <Halide solid electrolyte materials>
[0055] As described above, the halide solid electrolyte material 101 is a material containing Li, M and X. The element M and the element X are as described above. According to the above configuration, the ionic conductivity of the halide solid electrolyte material 101 is further improved, so the ionic conductivity of the ionic conductor material in Embodiment 1 can be further improved. As a result, when the ionic conductor material in Embodiment 1 is used in a battery, the charge and discharge efficiency of the battery can be improved. In addition, when the ionic conductor material in Embodiment 1 is used in a battery, the thermal stability of the battery can be improved. In addition, the halide solid electrolyte material 101 does not contain sulfur, so the ionic conductor material in Embodiment 1 can suppress the generation of hydrogen sulfide gas.
[0056] For example, the halide solid electrolyte material 101 may be a material represented by the following composition formula (1).
[0057] Li α M β X γ Formula (1)
[0058] In the above composition formula (1), α, β and γ are all values greater than 0. γ can be, for example, 4 or 6.
[0059] According to the above configuration, the ion conductivity of the halide solid electrolyte material 101 is improved, and thus the ion conductivity of the ion conductor material in Embodiment 1 can be improved. Therefore, when the ion conductor material in Embodiment 1 is used in a battery, the charge and discharge efficiency of the battery can be further improved.
[0060] In the above composition formula (1), the element M may include Y (=yttrium). That is, the halide solid electrolyte material 101 may include Y as a metal element.
[0061] The halide solid electrolyte material 101 containing Y can be represented by the following composition formula (2), for example.
[0062] Li a Me b Y c X6 type (2)
[0063] Among them, a, b and c can satisfy a+mb+3c=6, and c>0. Element Me is at least one selected from metal elements and metalloid elements other than Li and Y. m represents the valence of element Me. In addition, when element Me contains multiple elements, mb is the sum of the values obtained by multiplying the composition ratio of each element by the valence of the element. For example, when Me contains element Me1 and element Me2, and the composition ratio of element Me1 is b1 and the valence of element Me1 is m1, and the composition ratio of element Me2 is b2 and the valence of element Me2 is m2, mb=m1b1+m2b2. In the above composition formula (2), element X is at least one selected from F, Cl, Br, and I.
[0064] The element Me may be, for example, at least one selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, Gd, and Nb.
[0065] As the halide solid electrolyte material 101, for example, the following materials can be used. According to the following materials, the ion conductivity of the halide solid electrolyte material 101 is further improved, so the ion conductivity of the ion conductor material in Embodiment 1 can be further improved. Therefore, when the ion conductor material in Embodiment 1 is used in a battery, the charge and discharge efficiency of the battery can be further improved.
[0066] The halide solid electrolyte material 101 may be a material represented by the following composition formula (A1).
[0067] Li 6-3d Y d X6 type (A1)
[0068] In the composition formula (A1), the element X is at least one selected from the group consisting of Cl, Br, and I. In the composition formula (A1), d satisfies 0<d<2.
[0069] The halide solid electrolyte material 101 may be a material represented by the following composition formula (A2).
[0070] Li3YX6 formula (A2)
[0071] In the composition formula (A2), the element X is at least one selected from Cl, Br and I.
[0072] The halide solid electrolyte material 101 may be a material represented by the following composition formula (A3).
[0073] Li 3-3δ Y 1+δ Cl6 formula (A3)
[0074] However, in the composition formula (A3), δ satisfies 0<δ≤0.15.
[0075] The halide solid electrolyte material 101 may be a material represented by the following composition formula (A4).
[0076] Li 3-3δ Y 1+δ Br6 formula (A4)
[0077] However, in the composition formula (A4), δ satisfies 0<δ≤0.25.
[0078] The halide solid electrolyte material 101 may be a material represented by the following composition formula (A5).
[0079] Li 3-3δ+a Y 1+δ-a Me a Cl 6-x-y Br x I y Formula (A5)
[0080] However, in the composition formula (A5), the element Me is at least one selected from the group consisting of Mg, Ca, Sr, Ba and Zn.
[0081] In addition, the above composition formula (A5) satisfies:
[0082] -1<δ<2,
[0083] 0<a<3,
[0084] 0<(3-3δ+a),
[0085] 0<(1+δ-a),
[0086] 0≤x≤6,
[0087] 0≤y≤6, and
[0088] (x+y)≤6.
[0089] The halide solid electrolyte material 101 may be a material represented by the following composition formula (A6).
[0090] Li 3-3δ Y 1+δ-a Me a Cl 6-x-y Br x I y Formula (A6)
[0091] In the above composition formula (A6), the element Me is at least one selected from the group consisting of Al, Sc, Ga and Bi.
[0092] In addition, the above composition formula (A6) satisfies:
[0093] -1<δ<1,
[0094] 0<a<2,
[0095] 0<(1+δ-a),
[0096] 0≤x≤6,
[0097] 0≤y≤6, and
[0098] (x+y)≤6.
[0099] The halide solid electrolyte material 101 may be a material represented by the following composition formula (A7).
[0100] Li 3-3δ-a Y 1+δ-a Me a Cl 6-x-y Br x I y Formula (A7)
[0101] In the above composition formula (A7), the element Me is at least one selected from the group consisting of Zr, Hf and Ti.
[0102] In addition, the above composition formula (A7) satisfies:
[0103] -1<δ<1,
[0104] 0<a<1.5,
[0105] 0<(3-3δ-a),
[0106] 0<(1+δ-a),
[0107] 0≤x≤6,
[0108] 0≤y≤6, and
[0109] (x+y)≤6.
[0110] The halide solid electrolyte material 101 may be a material represented by the following composition formula (A8).
[0111] Li 3-3δ-2a Y 1+δ-a Me a Cl 6-x-y Br x I y Formula (A8)
[0112] In the above composition formula (A8), the element Me is at least one selected from Ta and Nb.
[0113] In addition, the above composition formula (A8) satisfies:
[0114] -1<δ<1,
[0115] 0<a<1.2,
[0116] 0<(3-3δ-2a),
[0117] 0<(1+δ-a),
[0118] 0≤x≤6,
[0119] 0≤y≤6, and
[0120] (x+y)≤6.
[0121] As the halide solid electrolyte material 101, more specifically, for example, Li3YX6, Li2MgX4, Li2FeX4, Li(Al, Ga, In)X4, Li3(Al, Ga, In)X6, etc. can be used. Among these materials, the element X is at least one selected from F, Cl, Br, and I. In addition, in the present disclosure, when the element in the formula is expressed as "(Al, Ga, In)", the expression represents at least one element selected from the element group in the brackets. That is, "(Al, Ga, In)" has the same meaning as "at least one selected from Al, Ga, and In". The same is true for other elements.
[0122] <Resin adhesive>
[0123] As described in the "Background Art" column, Patent Document 1 discloses a battery comprising a solid electrolyte and a thermoplastic elastomer into which a functional group is introduced. In the battery disclosed in Patent Document 1, the solid electrolyte is particularly a sulfide solid electrolyte or an oxide solid electrolyte. That is, the battery disclosed in Patent Document 1 comprises a mixture of a sulfide solid electrolyte or an oxide solid electrolyte and a resin binder having a modifying group. According to Patent Document 1, the battery disclosed in Patent Document 1 can have both a sealing strength having a replacement relationship and battery characteristics through this structure.
[0124] The inventors of the present invention have studied batteries comprising solid electrolyte materials and resin binders. As a result, the inventors of the present invention have found that when a halide solid electrolyte material is mixed with a resin binder having a modified group, the ionic conductivity of the solid electrolyte material is reduced and the charge and discharge efficiency of the battery is reduced. This problem can be considered to be caused by the reaction of the halide solid electrolyte material with the modified group of the resin binder, or the interaction of the halide solid electrolyte material with the modified group of the resin binder. If described in more detail, it can be considered that the reason is that the bonding site with high ionic bonding such as MX possessed by the halide solid electrolyte material, and the bonding site with high polarity formed by the electronegativity of the modified group of the resin binder, such as O or N, react or interact. In addition, it can be considered that such a phenomenon does not occur in the PS bond possessed by the sulfide solid electrolyte material, and the MO bond possessed by the oxide solid electrolyte material, and the bonding site with high covalent bonding. That is, it can be considered that the above-mentioned problem is a problem unique to the halide solid electrolyte material.
[0125] The inventors of the present invention have further conducted research based on the above-mentioned knowledge. As a result, it was found that by suppressing the amount of modified groups of the resin binder relative to the halide solid electrolyte material, specifically, making the amount ratio of the modified groups contained in the resin binder relative to the halide solid electrolyte material less than 0.0002, even if the halide solid electrolyte material and the resin binder are combined, the reduction in the ionic conductivity of the halide solid electrolyte material can be suppressed. As described above, in the ion conductor material 1000 in embodiment 1, the amount ratio of the modified groups contained in the resin binder 102 relative to the halide solid electrolyte material 101 is less than 0.0002. As a result, the ion conductor material 1000 in embodiment 1 can maintain the bonding strength of the halide solid electrolyte material 101 while improving the charge and discharge efficiency of the battery.
[0126] Hereinafter, “the amount ratio of the modifying group contained in the resin binder 102 to the halide solid electrolyte material 101 ” may be simply referred to as “the amount ratio of the modifying group”.
[0127] In addition, in the ion conductor material 1000 in Embodiment 1, the amount ratio of the modified group can be 0. That is, the resin binder 102 may not contain the modified group. By not containing the modified group in the resin binder 102, the reduction in the ion conductivity of the halide solid electrolyte material 101 can be further suppressed. Therefore, the ion conductor material 1000 in Embodiment 1 can maintain the bonding strength of the halide solid electrolyte material 101 while further improving the charge and discharge efficiency of the battery. In addition, in the ion conductor material 1000 in Embodiment 1, the amount ratio of the modified group can be greater than 0.
[0128] In the ion conductor material 1000 in Embodiment 1, if the amount ratio of the modifying group is 0.0002 or less, the resin binder 102 may contain a modifying group. If the amount ratio of the modifying group is 0.0002 or less, the ion conductor material 1000 in Embodiment 1 can maintain the bonding strength of the halide solid electrolyte material 101 while improving the charge and discharge efficiency of the battery.
[0129] As the resin binder 102 in the embodiment 1, for example, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polycarbonate, polyether sulfone, polyether ketone, polyether ether ketone, polyphenylene sulfide, hexafluoropolypropylene, styrene-butadiene rubber, carboxymethyl cellulose, and ethyl cellulose, etc. can be cited. In addition, copolymers containing two or more monomers selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, 1,1-vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, butadiene, styrene, pentafluoropropylene, fluoromethyl vinyl ether, acrylate, acrylic acid, and hexadiene can also be used. They can be used alone or in combination.
[0130] The resin adhesive 102 in the first embodiment is not particularly limited, but can be an elastomer based on the reason of excellent adhesion. In addition, the so-called elastomer is a polymer with elasticity. In addition, the elastomer used as the resin adhesive 102 can be a thermoplastic elastomer or a thermosetting elastomer. The resin adhesive 102 can include a thermoplastic elastomer. As an elastomer, for example, styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-ethylene-propylene-styrene copolymer (SEPS), styrene-ethylene-ethylene-propylene-styrene copolymer (SEEPS), butene rubber (BR), isoprene rubber (IR), chloroprene rubber (CR), nitrile rubber (NBR), styrene-butylene rubber (SBR), styrene-butadiene-styrene (SBS), styrene-isoprene-styrene (SIS), hydrogenated isoprene rubber (HIR), hydrogenated butyl rubber (HIIR), hydrogenated nitrile rubber (HNBR) and hydrogenated styrene-butylene rubber (HSBR) etc. can be cited. As thermoplastic elastomer, for example, SEBS, SEPS, SEEPS, SBS, SIS, etc. can be cited. In addition, two or more selected from them can be mixed and used. When the resin binder 102 contains a thermoplastic elastomer, when heat compression is performed during battery manufacturing, high filling of the ion conductor material 1000 can be achieved.
[0131] The thermoplastic elastomer contained in the resin binder 102 may be a styrene-based thermoplastic elastomer containing styrene. Since the styrene-based thermoplastic elastomer has high electrochemical resistance and high adhesive strength, it can improve the cycle performance of the battery.
[0132] The thermoplastic elastomer contained in the resin binder 102 may be SEBS. SEBS has high electrochemical resistance and high adhesive strength, and thus can further improve the cycle performance of the battery.
[0133] As the resin adhesive 102 in the first embodiment, TAFTEC manufactured by Asahi Kasei Corporation or the like can be used.
[0134] The modified group contained in the so-called resin binder 102 in the first embodiment is a functional group that is chemically modified by substitution or addition, etc., in whole or in part, with respect to the repeating unit of the polymer chain or at the end of the polymer chain. As the modified group, for example, a functional group containing an element such as O or N with high electronegativity can be cited, and polarity can be imparted to the resin binder by having such a functional group. As the modified group, for example, a carboxylic acid group, a maleic anhydride group, an acyl group, a hydroxyl group, a sulfonic group, a sulfanyl group, a phosphoric acid group, a phosphonic acid group, an isocyanate group, an epoxy group, a silyl group, an amino group, a nitrile group, and a nitro group can be cited.
[0135] As a method for adjusting the amount of modified groups in the resin binder 102 in Embodiment 1, control of the amount of modified groups introduced into the resin binder and dilution by adding an unmodified resin binder to a resin binder containing modified groups can be used.
[0136] The amount ratio of the modified group is obtained, for example, by the following method. The resin binder 102 is extracted with a solvent in which the halide solid electrolyte material 101 is insoluble and the resin binder 102 is soluble, such as an aromatic solvent such as toluene. With respect to the extracted resin binder 102, the amount of the modified group is obtained by infrared spectroscopy (IR method). On the other hand, the amount of the halide solid electrolyte material 101 that remains without being extracted is obtained. The amount ratio of the modified group can be obtained by dividing the measured value of the amount of the modified group by the amount of the halide solid electrolyte material 101.
[0137] When the amount of the halide solid electrolyte material 101, the acid value of all the resin components constituting the resin binder 102, and the mass ratio of these resin components are unclear, the amount of the halide solid electrolyte material 101, the acid value and the mass ratio of the resin components can be used instead of the above method to calculate the amount ratio of the modified group by the method described in the following examples.
[0138] In the ion conductor material 1000 in the first embodiment, the acid value of the resin binder 102 can be 1 mg-CH3ONa / g or less. Here, "mg-CH3ONa / g" is a unit of the amount of "CH3ONa" required to neutralize the modified group contained in 1 g of the target compound (here, the resin binder 102) in mg. By making the acid value of the resin binder 102 less than 1 mg-CH3ONa / g, the ion conductor material 1000 in the first embodiment can maintain the bonding strength of the halide solid electrolyte material 101 and improve the charge and discharge efficiency of the battery.
[0139] The acid value of the resin binder 102 can be determined by a titration method, for example, the titration method described in Japanese Patent No. 4946387.
[0140] The weight average molecular weight of the resin binder 102 in Embodiment 1 may be, for example, in the range of 1,000 to 1,000,000, or in the range of 10,000 to 500,000. When the weight average molecular weight of the resin binder 102 is 1,000 or more, sufficient bonding strength between the particles of the halide solid electrolyte material 101 can be obtained. When the weight average molecular weight of the resin binder 102 is 1,000,000 or less, the ion conduction between the particles of the halide solid electrolyte material 101 is not hindered by the resin binder 102, so that the charge and discharge characteristics of the battery can be improved. As the weight average molecular weight of the resin binder 102, for example, a weight average molecular weight of a polystyrene conversion value obtained by gel permeation chromatography (GPC) using chloroform as an eluent can be used.
[0141] The mixing method of the halide solid electrolyte material 101 and the resin binder 102 when manufacturing the ion conductor material 1000 in embodiment 1 is not particularly limited. For example, a method of mechanical crushing and mixing in a dry manner can be cited. If such a method is used, the ion conductor material 1000 in embodiment 1 can be easily manufactured. In addition, a wet method can be used in which the halide solid electrolyte material is dispersed in a resin binder material solution or a resin binder dispersion and then dried. If such a method is used, the resin binder and the halide solid electrolyte material can be easily and uniformly mixed, thereby improving the bonding strength of the halide solid electrolyte material. As a solvent used in the above method, a solvent that does not react with the halide solid electrolyte, such as an aromatic solvent such as toluene, can be used.
[0142] Next, a description will be given of a method for producing the halide solid electrolyte material 101. Here, an example of a method for producing the halide solid electrolyte material represented by the above composition formula (1) will be given.
[0143] First, prepare a variety of binary halide raw material powders according to the target composition. The so-called binary halide refers to a compound formed by two elements including a halogen element. For example, in the case of making Li3YCl6, raw material powder LiCl and raw material powder YCl3 are prepared in a molar ratio of 3:1. At this time, by selecting the type of raw material powder, the element type of "M" and "X" in the composition formula (1) can be determined. In addition, by adjusting the type of raw material powder, the mixing ratio of the raw material powder and the synthesis process, the values of "α", "β" and "γ" in the composition formula (1) can be adjusted.
[0144] After the raw material powders are mixed and crushed, the raw material powders are reacted with each other using a mechanochemical grinding method. Alternatively, the raw material powders can be mixed and crushed and then sintered in a vacuum or in an inert atmosphere. The sintering conditions can be, for example, sintering at a temperature of 100° C. to 550° C. for more than 1 hour. By these methods, a halide solid electrolyte material is obtained.
[0145] In addition, the composition of the crystal phase of the halide solid electrolyte material (that is, the crystal structure) can be adjusted or determined by the reaction method and reaction conditions of the raw material powders.
[0146] (Implementation Method 2)
[0147] Embodiment 2 will be described below. Explanations overlapping with those of Embodiment 1 described above will be appropriately omitted.
[0148] Figure 2 This is a cross-sectional view schematically showing the structure of a battery 2000 in the second embodiment.
[0149] The battery 2000 in the second embodiment includes a positive electrode 202 , a negative electrode 203 , and an electrolyte layer 201 .
[0150] At least one selected from the positive electrode 202 , the negative electrode 203 , and the electrolyte layer 201 includes the ion conductor material 1000 in the first embodiment described above.
[0151] The electrolyte layer 201 is disposed between the positive electrode 202 and the negative electrode 203 .
[0152] With the above configuration, the battery of Embodiment 2 can improve the charge and discharge efficiency.
[0153] In the battery 2000 in the second embodiment, the positive electrode 202 may include the ion conductor material 1000 in the first embodiment described above.
[0154] According to the above configuration, the charge and discharge efficiency of the battery can be further improved.
[0155] In the battery 2000 in the second embodiment, the electrolyte layer 201 may include the ion conductor material 1000 in the first embodiment described above.
[0156] Alternatively, the electrolyte layer 201 may be composed only of the ion conductor material 1000 in the first embodiment described above.
[0157] With the above configuration, the battery of Embodiment 2 can further improve the charge and discharge efficiency.
[0158] The electrolyte layer 201 is a layer containing an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. That is, the electrolyte layer 201 can be a solid electrolyte layer. As the solid electrolyte material contained in the electrolyte layer 201, for example, a sulfide solid electrolyte material, an oxide solid electrolyte material, a halide solid electrolyte material, a polymer solid electrolyte material, and a coordination compound hydride solid electrolyte material can be used. The solid electrolyte material can be, for example, a halide solid electrolyte material.
[0159] The term “oxide solid electrolyte material” in the present disclosure refers to a solid electrolyte material containing oxygen. Here, the oxide solid electrolyte material may further contain anions other than sulfur and halogen elements as anions other than oxygen.
[0160] As described in the first embodiment, the “halide solid electrolyte material” corresponds to the solid electrolyte material 101 included in the ion conductor material 1000 in the first embodiment.
[0161] As sulfide solid electrolyte materials, for example, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, and Li 10 GeP2S 12 In addition, LiX, Li2O, MO can be added to them. q and / or Li p MO q etc. Among them, the element X in "LiX" is at least one selected from F, Cl, Br and I. In addition, "MO q ” and “Li p MO q The element M in " is at least one selected from P, Si, Ge, B, Al, Ga, In, Fe and Zn. In addition, "MO q ” and “Li p MO q "In this equation, p and q are both natural numbers.
[0162] As oxide solid electrolyte materials, for example, NASICON-type solid electrolyte materials represented by LiTi2(PO4)3 and its element substitution products, (LaLi)TiO3-based perovskite-type solid electrolyte materials, and Li 14 ZnGe4O 16 , LISICON type solid electrolyte materials represented by Li4SiO4, LiGeO4 and their element substitution products, Li7La3Zr2O 12Garnet-type solid electrolyte materials represented by Li3PO4 and its element-substituted bodies, Li3PO4 and its N-substituted bodies, glasses based on Li-BO compounds such as LiBO2 and Li3BO3 and added with Li2SO4, Li2CO3, etc., and glass ceramics, etc.
[0163] As a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound can have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt. Therefore, the ion conductivity can be further improved. As a lithium salt, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be used. One lithium salt can be used alone, or two or more can be used in combination.
[0164] As the coordination compound hydride solid electrolyte, for example, LiBH4-LiI, LiBH4-P2S5, etc. can be used.
[0165] The electrolyte layer 201 may contain a solid electrolyte material as a main component. That is, the electrolyte layer 201 may contain, for example, 70% or more (70% by mass or more) of the solid electrolyte material relative to the entire electrolyte layer 201 in terms of mass ratio.
[0166] According to the above configuration, the charge and discharge characteristics of the battery can be further improved.
[0167] In addition, the electrolyte layer 201 contains a solid electrolyte material as a main component, and may further contain inevitable impurities, or starting materials, by-products, and decomposition products used when synthesizing the solid electrolyte material.
[0168] In addition, the electrolyte layer 201 may contain, for example, 100% (100 mass %) of the solid electrolyte material in terms of the mass ratio relative to the entire electrolyte layer 201 excluding impurities inevitably mixed therein.
[0169] According to the above configuration, the charge and discharge characteristics of the battery can be further improved.
[0170] In addition, the electrolyte layer 201 may include two or more of the materials listed as the solid electrolyte material. For example, the electrolyte layer 201 may include a halide solid electrolyte material and a sulfide solid electrolyte material.
[0171] The thickness of the electrolyte layer 201 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 201 is 1 μm or more, the possibility of a short circuit between the positive electrode 202 and the negative electrode 203 becomes low. In addition, when the thickness of the electrolyte layer 201 is 300 μm or less, the operation at high output becomes easy. That is, if the thickness of the electrolyte layer 201 is appropriately adjusted, sufficient safety of the battery can be ensured, and the battery can be operated at high output.
[0172] The shape of the solid electrolyte material included in the battery 2000 is not limited. The shape of the solid electrolyte material may be, for example, needle-shaped, spherical, ellipsoidal, etc. The shape of the solid electrolyte material may be, for example, particle-shaped.
[0173] At least one of the positive electrode 202 and the negative electrode 203 may include an electrolyte material, for example, a solid electrolyte material. As the solid electrolyte material, the solid electrolyte material exemplified as the material constituting the electrolyte layer 201 can be used. According to the above configuration, the lithium ion conductivity inside the positive electrode 202 or the negative electrode 203 becomes high, and operation at high output can be performed.
[0174] The positive electrode 202, for example, contains a material having the property of absorbing and releasing metal ions (for example, lithium ions) as a positive electrode active material. As the positive electrode active material, for example, transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, transition metal oxynitrides, etc. containing lithium can be used. As examples of transition metal oxides containing lithium, Li(Ni, Co, Al)O2, LiCoO2, etc. can be cited. For example, when a transition metal oxide containing lithium is used as a positive electrode active material, the manufacturing cost can be made cheap and the average discharge voltage can be increased. In addition, in order to increase the energy density of the battery, lithium nickel cobalt manganese oxide can be used as a positive electrode active material. For example, the positive electrode active material can be Li(Ni, Co, Mn)O2.
[0175] When the solid electrolyte material included in the positive electrode 202 is in a particle shape (e.g., spherical), the median particle size of the solid electrolyte material may be 100 μm or less. When the median particle size of the solid electrolyte material is 100 μm or less, the positive electrode active material and the solid electrolyte material may be well dispersed in the positive electrode 202. As a result, the charge and discharge characteristics of the battery are improved.
[0176] The median particle size of the solid electrolyte material included in the positive electrode 202 may be smaller than the median particle size of the positive electrode active material. This allows the solid electrolyte material and the positive electrode active material to be well dispersed.
[0177] The median particle size of the positive electrode active material can be 0.1 μm or more and 100 μm or less. When the median particle size of the positive electrode active material is 0.1 μm or more, the positive electrode active material and the solid electrolyte material can be well dispersed in the positive electrode 202. As a result, the charge and discharge characteristics of the battery are improved. When the median particle size of the positive electrode active material is 100 μm or less, the lithium diffusion rate in the positive electrode active material is increased. Therefore, the battery can operate at high output.
[0178] The median diameter is the particle diameter at which the cumulative volume in the volume-based particle size distribution is 50%. The volume-based particle size distribution is obtained by a laser diffraction scattering method. The same applies to the following other materials.
[0179] When the volume fraction of the positive electrode active material and the solid electrolyte material contained in the positive electrode 202 is set to "v1: 100-v1", 30≤v1≤95 can be satisfied. Among them, v1 represents the volume fraction of the positive electrode active material when the total volume of the positive electrode active material and the solid electrolyte material contained in the positive electrode 202 is set to 100. When 30≤v1 is satisfied, it is easy to ensure sufficient energy density of the battery. When v1≤95 is satisfied, the operation of the battery at high output becomes easier.
[0180] The thickness of the positive electrode 202 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode is 10 μm or more, it is easy to ensure sufficient battery energy density. When the thickness of the positive electrode is 500 μm or less, it is easier to operate the battery at high output.
[0181] The negative electrode 203, for example, contains a material having the property of absorbing and releasing metal ions (for example, lithium ions) as a negative electrode active material. As the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used. The metal material can be a single metal or an alloy. As metal materials, lithium metal, lithium alloys, etc. can be mentioned. As carbon materials, natural graphite, coke, incompletely graphitized carbon, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. can be mentioned. By using silicon (Si), tin (Sn), silicon compounds, tin compounds, etc., the capacity density can be improved.
[0182] The median particle size of the negative electrode active material can be greater than 0.1 μm and less than 100 μm. When the median particle size of the negative electrode active material is greater than 0.1 μm, the negative electrode active material and the solid electrolyte material can be well dispersed in the negative electrode 203. As a result, the charge and discharge characteristics of the battery are improved. When the median particle size of the negative electrode active material is less than 100 μm, the lithium diffusion rate in the negative electrode active material is increased. Therefore, the battery can operate at high output.
[0183] The median particle size of the negative electrode active material may be larger than that of the solid electrolyte material, so that the solid electrolyte material and the negative electrode active material can be well dispersed.
[0184] When the volume fraction of the negative electrode active material and the solid electrolyte material contained in the negative electrode 203 is set to "v2: 100-v2", 30≤v2≤95 can be satisfied. Among them, v2 represents the volume fraction of the negative electrode active material when the total volume of the negative electrode active material and the solid electrolyte material contained in the negative electrode 203 is set to 100. When 30≤v2 is satisfied, it is easy to ensure sufficient energy density of the battery. When v2≤95 is satisfied, the operation of the battery at high output becomes easier.
[0185] The thickness of the negative electrode 203 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode is 10 μm or more, it is easy to ensure sufficient battery energy density. When the thickness of the negative electrode is 500 μm or less, it is easier to operate the battery at high output.
[0186] The positive electrode active material and the negative electrode active material may be coated with a coating material in order to reduce the interface resistance between each active material and the solid electrolyte material. As the coating material, a material with low electronic conductivity may be used. As the coating material, an oxide material and an oxide solid electrolyte material may be used.
[0187] As the oxide material used for the coating material, for example, SiO2, Al2O3, TiO2, B2O3, Nb2O5, WO3, and ZrO2 can be used.
[0188] As the oxide solid electrolyte material used as the coating material, for example, Li-Nb-O compounds such as LiNbO3, Li-BO compounds such as LiBO2 and Li3BO3, Li-Al-O compounds such as LiAlO2, Li-Si-O compounds such as Li4SiO4, Li2SO4, Li4Ti5O 12 Li-Ti-O compounds, Li-Zr-O compounds, Li-Mo-O compounds, Li-V-O compounds, Li-WO compounds, etc. Oxide solid electrolyte materials have high ion conductivity and high high potential stability. Therefore, by using oxide solid electrolyte materials as coating materials, the charge and discharge efficiency of the battery can be further improved.
[0189] At least one selected from the positive electrode 202, the electrolyte layer 201, and the negative electrode 203 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the transfer of lithium ions and improving the output characteristics of the battery.
[0190] The non-aqueous electrolyte solution includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, and fluorine solvents can be used. Examples of cyclic carbonate solvents include ethylene carbonate, propylene carbonate, and butylene carbonate. Examples of chain carbonate solvents include dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate. Examples of cyclic ether solvents include tetrahydrofuran, 1,4-dihydrofuran, and 1,4-dihydrofuran. As chain ether solvents, 1,2-dimethoxyethane, 1,2-diethoxyethane, etc. can be mentioned. As cyclic ester solvents, γ-butyrolactone, etc. can be mentioned. As chain ester solvents, methyl acetate, etc. can be mentioned. As fluorine solvents, fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, ethyl fluoromethyl carbonate, dimethyl fluorocarbonate, etc. can be mentioned. As non-aqueous solvents, one non-aqueous solvent selected from them can be used alone, or a mixture of two or more non-aqueous solvents selected from them can be used.
[0191] The non-aqueous electrolyte may contain at least one fluorine solvent selected from the group consisting of fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, ethyl fluoromethyl carbonate, and dimethyl fluorocarbonate.
[0192] As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be cited. As lithium salts, one lithium salt selected from them can be used alone, or a mixture of two or more lithium salts selected from them can be used. The concentration of the lithium salt can be, for example, 0.5 mol / liter or more and 2 mol / liter or less.
[0193] As the gel electrolyte, a material containing a non-aqueous electrolyte in a polymer material can be used. Examples of the polymer material include polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, and polymers having ethylene oxide bonds.
[0194] The cations constituting the ionic liquid may be tetraalkylammonium, tetraalkyl Aliphatic chain quaternary cations, pyrrolidine Morpholine Imidazolin Tetrahydropyrimidine Piperazine Piperidine Aliphatic cyclic ammonium, pyridine Imidazole The anions that make up the ionic liquid can be PF6 - 、BF4 - , SbF 6- - 、AsF6 - 、SO3CF3 - 、N(SO2F)2 - 、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2CF3)(SO2C4F9) - 、C(SO2CF3)3 - etc. The ionic liquid may contain a lithium salt.
[0195] At least one of the positive electrode 202 and the negative electrode 203 may include a conductive auxiliary agent for the purpose of improving electronic conductivity. As the conductive auxiliary agent, for example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black and Ketjen black, conductive fibers such as carbon fibers and metal fibers, conductive powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, conductive polymers such as polyaniline, polypyrrole and polythiophene, etc. can be used. If a carbon material is used as a conductive auxiliary agent, low cost can be achieved.
[0196] Examples of the shape of the battery include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, and a laminate shape.
[0197] The battery in Embodiment 2 can be manufactured, for example, by separately preparing materials for forming a positive electrode, materials for forming an electrolyte layer, and materials for forming a negative electrode, and making a stacked body in which a positive electrode, an electrolyte layer, and a negative electrode are sequentially arranged by a known method.
[0198] (Example)
[0199] The details of the present disclosure are described below using examples and comparative examples. In addition, the ion conductor material and battery of the present disclosure are not limited to the following examples.
[0200] <Example 1>
[0201] [Production of halide solid electrolyte materials]
[0202] In an argon glove box with a dew point below -60°C, YCl3, LiCl and LiBr as raw material powders were weighed in a molar ratio of YCl3:LiCl:LiBr=1:1:2. Then, these raw material powders were mixed, and the resulting mixture was calcined at 520°C for 2 hours using an electric furnace to obtain Li3YBr2Cl4 (hereinafter referred to as "LYBC") as a halide solid electrolyte material. Parachlorotoluene was added to the obtained LYBC, and after pulverizing it using a wet fine pulverizer / disperser, it was dried to obtain LYBC fine powder (median particle size D 50 =0.4μm).
[0203] [Production of sulfide solid electrolyte materials]
[0204] In an argon glove box with a dew point below -60°C, Li2S and P2S5 as raw material powders were weighed in a molar ratio of Li2S:P2S5=75:25. These raw material powders were crushed and mixed in a mortar. Then, the resulting mixture was ground at 510 rpm for 10 hours using a planetary ball mill (manufactured by Freeze, P-7 type). The resulting glassy solid electrolyte was heat treated at 270°C for 2 hours in an inert atmosphere. Through the above, Li2S-P2S5 (hereinafter referred to as "LPS") as a glass-ceramic solid electrolyte material was obtained.
[0205] [Fabrication of positive electrode including ion conductor material]
[0206] In an argon glove box with a dew point below -60°C, LYBC powder and unmodified SEBS (produced by Asahi Kasei Corporation, TAFTEC N504, acid value 0 mg-CH3ONa / g) are weighed at a mass ratio of LYBC powder: unmodified SEBS = 1:0.022. The weighed LYBC powder and unmodified SEBS are dissolved or dispersed in a solvent, tetralin, to prepare an ion conductor material slurry. In the ion conductor material, the halide solid electrolyte material is composed of LYBC, and the resin binder is composed of unmodified SEBS. Next, the ion conductor material slurry and Li(Ni, Co, Mn)O2 are weighed in such a way that the mass ratio of LYBC to Li(Ni, Co, Mn)O2 becomes LYBC:Li(NiCoMn)O2=1:4.42. The weighed ion conductor material slurry and Li (Ni, Co, Mn) O2 were kneaded at 1600 rpm for 6 minutes using a rotation / revolution mixer (made by THINKY, ARE-310) to produce a positive electrode slurry. Copper foil (thickness 12 μm) was used as a current collector. The positive electrode slurry was applied on the copper foil and dried at 100° C. in a vacuum for 1 hour to produce a positive electrode.
[0207] [Manufacturing of Secondary Batteries]
[0208] In an insulating outer cylinder, a positive electrode punched into φ9.2 mm, 20 mg of LYBC, and 60 mg of LPS were stacked in sequence. The resulting stack was press-formed at a pressure of 740 MPa to obtain a stack of the positive electrode and the solid electrolyte layer. In the resulting stack of the positive electrode and the solid electrolyte layer, the thickness of the positive electrode was 60 μm.
[0209] Next, metal In (thickness 200 μm), metal Li (thickness 200 μm), and metal In (thickness 200 μm) were stacked in sequence on the side opposite to the side of the solid electrolyte layer that was in contact with the positive electrode. The resulting stack was press-formed at a pressure of 80 MPa to obtain a two-pole electrochemical cell consisting of a positive electrode, a solid electrolyte layer, and a counter electrode. In this electrochemical cell, the positive electrode is a working electrode, and the counter electrode is a reference electrode.
[0210] Next, stainless steel current collectors were placed above and below the electrochemical cell, and current collecting leads were attached to the stainless steel current collectors.
[0211] Next, an insulating ferrule is used to block and seal the inside of the insulating outer cylinder from the outside air atmosphere.
[0212] Finally, the electrochemical cell was fastened from above and below with four bolts, thereby applying a surface pressure of 150 MPa to the electrochemical cell.
[0213] Through the above, the secondary battery of Example 1 was prepared. In the secondary battery of Example 1, the positive electrode contains the ion conductor material disclosed in the present invention. In the ion conductor material contained in the secondary battery of Example 1, the amount ratio of the modifying group contained in the resin binder to the halide solid electrolyte material is 0. The acid value of the resin binder in the ion conductor material is 0.
[0214] <Example 2>
[0215] In the preparation of the ion conductor material slurry, LYBC powder, unmodified SEBS (Taftec N504 manufactured by Asahi Kasei Corporation, acid value 0 mg-CH3ONa / g), and maleic anhydride modified SEBS (Taftec M1913 manufactured by Asahi Kasei Corporation, acid value 10 mg-CH3ONa / g) were weighed at a mass ratio of LYBC powder: unmodified SEBS: maleic anhydride modified SEBS = 1: 0.020: 0.0022. In the ion conductor material, the halide solid electrolyte material is composed of LYBC, and the resin binder is composed of unmodified SEBS and maleic anhydride modified SEBS. The other items are implemented in the same manner as the method of the above-mentioned Example 1 to obtain the secondary battery of Example 2.
[0216] Regarding the ion conductor material contained in the secondary battery of Example 2, the mass ratio of the modified group contained in the resin binder to the halide solid electrolyte material is calculated by the following formula (3) using the acid values of the unmodified SEBS and maleic anhydride-modified SEBS constituting the resin binder. The mass ratio of the modified group contained in the resin binder to LYBC as the halide solid electrolyte material calculated by the following formula (3) is 0.0002.
[0217] Amount ratio of modified groups = [{(acid value of unmodified SEBS) × (content of unmodified SEBS)} / {(molecular weight of CH3ONa = 54.02 g / mol) × 1000} + {(acid value of maleic anhydride-modified SEBS) × (content of maleic anhydride-modified SEBS)} / {(molecular weight of CH3ONa × 1000}] / {(content of LYBC) / (molecular weight of LYBC = 411.35 g / mol)} (3)
[0218] In addition, regarding the ion conductor material included in the secondary battery of Example 2, the acid value of the resin binder was calculated by the following formula (4). The acid value of the resin binder calculated by the following formula (4) was 1 mg-CH3ONa / g.
[0219] Acid value of resin binder = {(acid value of unmodified SEBS) × (mass content of unmodified SEBS) + (acid value of maleic anhydride-modified SEBS) × (mass content of maleic anhydride-modified SEBS)} / {(mass content of unmodified SEBS) + (mass content of maleic anhydride-modified SEBS)} (4)
[0220] <Comparative Example 1>
[0221] In the preparation of the ion conductor material slurry, LYBC powder, unmodified SEBS (Taftec N504 manufactured by Asahi Kasei Corporation, acid value 0 mg-CH3ONa / g), and maleic anhydride modified SEBS (Taftec M1913 manufactured by Asahi Kasei Corporation, acid value 10 mg-CH3ONa / g) were weighed at a mass ratio of LYBC powder: unmodified SEBS: maleic anhydride modified SEBS = 1: 0.017: 0.0043. In the ion conductor material, the halide solid electrolyte material is composed of LYBC, and the resin binder is composed of unmodified SEBS and maleic anhydride modified SEBS. The other items are implemented in the same manner as the method of Example 1 above, and the secondary battery of Comparative Example 1 is obtained.
[0222] Regarding the ion conductor material contained in the secondary battery of Comparative Example 1, the amount ratio of the modified group contained in the resin binder to the halide solid electrolyte material was calculated using the acid values of the unmodified SEBS and maleic anhydride-modified SEBS constituting the resin binder by the above formula (3) used in Example 2. The amount ratio of the modified group contained in the resin binder to LYBC as the halide solid electrolyte material calculated by the above formula (3) was 0.0003.
[0223] In addition, regarding the ion conductor material included in the secondary battery of Comparative Example 1, the acid value of the resin binder was determined by the above formula (4) used in Example 2. The acid value of the resin binder calculated by the above formula (4) was 2 mg-CH3ONa / g.
[0224] <Comparative Example 2>
[0225] In the preparation of the ion conductor material slurry, LYBC powder and maleic anhydride modified SEBS (manufactured by Asahi Kasei Corporation, タフテックM1913, acid value 10mg-CH3ONa / g) were weighed at a mass ratio of LYBC powder: maleic anhydride modified SEBS = 1:0.022. In the ion conductor material, the halide solid electrolyte material is composed of LYBC, and the resin binder is composed of maleic anhydride modified SEBS. The other items are implemented in the same manner as the method of Example 1 above, and the secondary battery of Comparative Example 2 is obtained.
[0226] Regarding the ion conductor material contained in the secondary battery of Comparative Example 2, the mass ratio of the modified group contained in the resin binder to the halide solid electrolyte material was calculated by the following formula (5) using the acid value of the maleic anhydride-modified SEBS constituting the resin binder. The mass ratio of the modified group contained in the resin binder to LYBC as the halide solid electrolyte material calculated by the following formula (5) was 0.002.
[0227] Modification group amount ratio = [{(acid value of maleic anhydride modified SEBS) × (mass content of maleic anhydride modified SEBS)} / {(molecular weight of CH3ONa × 1000}] / {(weight content of LYBC) / (molecular weight of LYBC)} (5)
[0228] In addition, regarding the ion conductor material included in the secondary battery of Comparative Example 2, the acid value of the resin binder was 10 mg-CH3ONa / g, which is the acid value of maleic anhydride-modified SEBS.
[0229] <Battery Evaluation>
[0230] [Charge and discharge test]
[0231] Using the batteries of Example 1, Example 2, Comparative Example 1, and Comparative Example 2, respectively, a charge and discharge test was carried out under the following conditions.
[0232] The battery was placed in a constant temperature chamber at 25°C.
[0233] The battery was charged to a voltage of 3.7 V (vs LiIn) at a current density of a current value at a rate of 0.05 C (20 hour rate) relative to the theoretical capacity of the positive electrode active material (Li(Ni, Co, Mn)O2). Next, the battery was discharged to a voltage of 1.9 V (vs LiIn) at a current density of a current value at a rate of 0.05 C in the same manner.
[0234] The above results show the charge capacity, discharge capacity and charge / discharge efficiency (=(discharge capacity / charge capacity)×100) of the batteries of Example 1, Example 2, Comparative Example 1 and Comparative Example 2. Table 1 shows the results.
[0235] Table 1
[0236]
[0237] <Investigation>
[0238] By comparing the results of Example 1 and Example 2 shown in Table 1 with the results of Comparative Examples 1 and Comparative Examples 2, it was confirmed that in the case of a battery using an ion conductor material in which the molar ratio of the modified group contained in the resin binder to LYBC is 0.0002 or less, a charging capacity close to the theoretical capacity of 200 mAh / g as the positive electrode is shown, and the charge and discharge efficiency of the battery is improved.
[0239] It has been confirmed from the above that the charge and discharge efficiency of the battery is improved by using the ion conductor material disclosed in the present invention. In addition, the so-called ion conductor material disclosed in the present invention is the following ion conductor material, which comprises: a solid electrolyte material containing Li, M and X and a resin binder, wherein the M is at least one selected from metal elements and metalloid elements other than Li, and the X is at least one selected from F, Cl, Br and I, and the amount ratio of the modified group contained in the resin binder to the solid electrolyte is 0.0002 or less.
[0240] Industrial Availability
[0241] The battery disclosed herein can be used as, for example, an all-solid lithium ion secondary battery or the like.
[0242] Description of Reference Numerals
[0243] 1000 Ion Conductor Materials
[0244] 101 Solid Electrolyte Materials
[0245] 102 resin adhesive
[0246] 2000 battery
[0247] 201 electrolyte layer
[0248] 202 positive electrode
[0249] 203 negative electrode.
Claims
1. An ion conductor material comprising a solid electrolyte material and a resin binder, The solid electrolyte material comprises Li, M, and X, The M is at least one selected from metal elements and metalloid elements other than Li, The X is at least one selected from F, Cl, Br and I, The amount ratio of the modifying group contained in the resin binder to the solid electrolyte material is greater than 0 and is 0.0002 or less.
2. The ion conductor material according to claim 1, wherein the solid electrolyte material is represented by the following composition formula (1): Li α M β X γ Formula (1) in, The α, β, and γ are all values greater than 0. The ion conductor material according to claim 1 , wherein M comprises yttrium. 4 . The ion conductor material according to claim 1 , wherein the resin binder comprises a thermoplastic elastomer. The ion conductor material according to claim 4 , wherein the thermoplastic elastomer comprises a styrene unit. The ion conductor material according to claim 5 , wherein the thermoplastic elastomer is a styrene-ethylene-butylene-styrene copolymer.
7. The ion conductor material according to any one of claims 1, 2, 5, and 6, wherein the acid value of the resin binder is less than 1 mg-CH3ONa / g.
8. A battery comprising: positive electrode; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode; At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the ion conductor material according to any one of claims 1 to 7.
Citation Information
Patent Citations
JP1974046387A
All-solid battery
WO2017217079A1
Solid electrolyte material, and cell
WO2018025582A1